Screening and Counseling for Tobacco Use in Student Health Clinics: Reports of Health Care Providers. Issue 1 (September 2015) - Sutfin, Erin L.; Swords, Darden C.; Song, Eun-Young; Reboussin, Beth A.; Helme, Donald; Klein, Elizabeth; Wolfson, Mark
Purpose: To assess tobacco screening and counseling in student health clinics, including facilitators, barriers, and associations with campus- and state-level variables. Design: We conducted a mixed-methods study with an online survey and qualitative interviews. Setting: Study setting was student health clinics on college campuses. Subjects: Subjects included 71 clinic directors or designees from 10 Southeastern states (quantitative survey) and 8 directors or designees from 4 Southeastern states (qualitative interviews). Measures: Quantitative measures included demographics, screening and counseling practices, clinic-level supports for such practices, perceptions of tobacco on campus, institution size, public/private status, state tobacco farming revenue, and state tobacco control funding. Qualitative measures included barriers and facilitators of tobacco screening and counseling practices. Analysis: Logistic and linear regression models assessed correlates of screening and counseling. Qualitative data were analyzed using multistage interpretive thematic analysis. Results: A total of 55% of online survey respondents reported that their clinics screen for tobacco at every visit, whereas 80% reported their clinics offer counseling and pharmacotherapy. Barriers included lack of the following: time with patients, relevance to chief complaint, student self-identification as a tobacco user, access to pharmacotherapy, and interest in quitting among smokers. In multivariable models, more efforts to reduce tobacco use, student enrollment, and state-level cash receipts for tobacco were positively associated with clinic-level supports. Conclusion: This study highlights missed opportunities for screening. Although reports of counseling were higher, providers identified many barriers.